ANALISIS KEMAMPUAN KOGNITIF SISWA DALAM MENYELESAIKAN OPERASI HITUNG PENJUMLAHAN DAN PENGURANGAN BERSUSUN PADA PESERTA DIDIK KELAS II SD NEGERI 010110 AMBALUTU - Ananda Revalina; Nita Kurnia Sari; Anim Anim; Juliyani Safika Dewi; Mufti Annisah Khairani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
The purpose of this study is to examine the cognitive abilities of students in learning addition and subtraction operations with carrying and borrowing in Grade II at SD Negeri 010110 Ambalutu. This research used a descriptive qualitative method. Data were collected through tests on students’ abilities in performing addition and subtraction operations. The subjects of this study were Grade II students of SD Negeri 010110 Ambalutu, while the object of the research was the teaching and learning of addition and subtraction with carrying and borrowing. The population of this study consisted of 26 students. The collected data were analyzed using data reduction, data presentation, and drawing conclusions. The results show that students’ mastery of addition and subtraction operations with carrying and borrowing is uneven. Many students are not careful when counting objects in pictures. Some students do not pay sufficient attention to the images, resulting in counts that are either less or more than the actual number. Several students also make mistakes in writing the forms of addition or subtraction with carrying and borrowing. In addition, some students forget to write the carry-over number when the sum of the units exceeds 10. Overall, students’ cognitive abilities in solving addition and subtraction with carrying and borrowing are in the fair category. The most common mistakes occur in questions that combine numbers and pictures, as students are not yet able to transform visual information into mathematical symbols. Therefore, the use of concrete media, routine practice, and a step-by-step approach is needed to help students improve their ability to perform structured arithmetic operations.